Early Screening for Retinopathy of Prematurity to Improve Visual Outcome in Preterm Babies - Manjunath C.B; Kotinatot S.C; Anand Vinekar; Pradeep G.C.M (JCDR Research and Publications Pvt. Ltd., 2013)
Background: Retinopathy of Prematurity(ROP) is a major cause of blindness in children in the developing world. Various guidelines have been established to screen routinely all preterm babies to prevent the development of ROP. The debate of ideal time to screen the babies for ROP is ongoing with conflicting results among various studies. Aims and Objectives: To investigate the utility of commencing Retinopathy of Prematurity(ROP) screening before three weeks after birth to detect severe, treatment grade ROP in preterm babies to improve visual outcome in preterm neonates. Material and Methods: A prospective study of 66 consecutive inborn premature infants screened for ROP was done. All preterm babies less than 2000grams/<34 weeks were screened from second week after birth. Demographic data, clinical profile of stage, type of ROP and age at diagnosis and treatment were analyzed. Results: The mean birth weight and gestational ages of the 66 infants were 1155 grams and 29.6 weeks respectively. 19(28.78%) infants had treatment grade ROP all of which underwent laser photocoagulation for treatment. Of these, 11 infants (58%) had type 1 and 8 infants (42%) had Aggressive Posterior Retinopathy Of Prematurity (APROP) and were lasered after a mean postnatal age of 3.9 weeks. Eight infants (42%) (4 with type 1 & 4 with APROP) were found to have treatment grade ROP before 3 weeks of life and were treated at mean age of 2.6 weeks. The mean birth weight of these early detected cases was 1070 grams and mean gestational age was 29.5 weeks respectively. All treated cases had a favorable outcome. Conclusion: Commencing ROP screening by 2nd week of life for babies <30 weeks or <1000 grams babies will help to improve the visual outcome in preterm babies with this dreaded morbidity.